PENDAMPINGAN AKUNTABILITAS KINERJA KEUANGAN DAN OPERASIONAL PD. BELEDAG DUA PUTRA DALAM PENINGKATAN EFISIENSI USAHA BERBASIS UMKM DI KABUPATEN CIAMIS - Susi Riani; Mugni Muhit; Wawan Anwar Sadat (Jurnal Istimā, 2025)
This service activity aims to increase the accountability and efficiency of PD's business. Beledag Dua Putra through financial and operational performance evaluation assistance. Assistance is carried out with a qualitative descriptive approach through financial statement analysis and field observation during June 2025. Activities include identification of cost structures, calculation of profit margins, as well as observation of production processes and marketing strategies. The results of the activity showed that PD. Beledag Dua Putra has a total turnover of IDR 49,390,050, with a profit margin of IDR 10,544,000 and a total expenditure of IDR 39,944,800. Although the business still shows a net profit, high operating expenses are the main obstacle in maintaining profitability. Through this assistance, business actors gain a better understanding of financial management, production cost efficiency, and digital-based sales increase strategies. This activity is expected to strengthen the competitiveness of local MSMEs through more accountable and sustainable business practices.